Effect of Lactation Diets Containing a Cheese Co-product on Sow and Litter Performance - Grady A. Privett; Diego A. Lopez; Jason C. Woodworth; Jordan T. Gebhardt; Katelyn N. Gaffield; Robert D. Goodband; Mike D. Tokach; Joel M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 86 sows (DNA 241, DNA Genetics, Columbus, NE) were used to determine the effects of a cheese co-product (Pro88; Key Manufacturing, Paris, IL) added to lactation diets on sow and litter performance. Sows, in three separate farrowing groups (approximately 43 ± 1 sows per group), were moved into the farrowing house and blocked by parity on d 112 ± 1 of gestation. They were then assigned to one of two dietary treatments that consisted of a control diet or the control with 4% added cheese co-product. Diets were formulated to be balanced for amino acids and minerals, but not for energy. There were 44 sows fed the control diet and 42 sows fed the diet with the cheese co-product. Sows were fed 6 lb of the control diet until farrowing and then were switched to their assigned treatment diet on d 2 of lactation after cross-fostering was completed. Sows were given ad libitum access to their assigned treatment diet until weaning (approximately d 18 of lactation). The addition of a cheese co-product in lactation diets did not affect sow weight, backfat, or loin depth change from entry to weaning. As expected, there were no differences after cross-fostering for the d 2 litter size, litter weight, and litter weight coefficient of variation (CV) as treatment diets had not been fed. Dietary treatment did not affect sow ADFI or their subsequent wean-to-estrus interval. Litter size at weaning, prewean mortality, and piglet and litter weights at weaning were not affected by dietary treatment. In conclusion, the addition of a cheese co-product in lactation diets did not influence sow or litter performance.
Keywords: cheese co-product; litter; sow